Small polyhedron reconnection for mesh improvement and its implementation based on advancing front technique - J. Liu; Chen, Y. Q.; Sun, S. L. (International Journal for Numerical Methods in EngineeringInternational Journal for Numerical Methods in Engineering, 2009)
Local transformation, or topological reconnection, is one of the effective procedures for mesh improvement method, especially for three-dimensional tetrahedral mesh. The most frequently used local transformations for tetrahedral mesh are so-called elementary flips, such as 2-3 flip, 3-2 flip. 2-2 flip, and 4-4 flip. Owing to the reason that these basic transformations simply make a selection from several possible configurations within a relatively small region, the improvement of mesh quality is confined. In order to further improve the quality of mesh, the authors recently suggested a new local transformation operation, small polyhedron reconnection (SPR) operation, which seeks for the optimal tetrahedralization of a polyhedron with a certain number of nodes and faces (typically composed of 20-40 tetrahedral elements).This paper is an implementation of the suggested method. The whole process to improve the mesh quality by SPR operation is presented; in addition, some strategies, similar to those used in advancing front technique, are introduced to speed up the operation. The numerical experiment shows that SPR operation is quite effective in mesh improvement and more suitable than elementary flips when combined with smoothing approach. The operation can be applied to practical problems, gaining high mesh quality with acceptable cost for computational time. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: advancing front technique; algorithm; construction; generation; local transformation; mesh improvement; optimal tetrahedralization; Optimization; small polyhedron reconnection (spr); tetrahedral mesh; tetrahedral meshes; triangulations